Средоточие останков оксибионтов и банк живых спор высших грибов и диатомовых в донных отложениях сероводородной батиали Черного моря - Зайцев, Ю.П.; Поликарпов, Г.Г.; Егоров, В.Н.; Александров, Б.Г.; Гаркуша, О.П.; Копытина, Н.И.; Курилов, А.В.; Нестерова, Д.А.; Нидзвецкая, Л.М.; Никонова, С.Е.; Поликарпов, И.Г.; Поповичев, В.Н.; et al. (Видавничий дім "Академперіодика" НАН України, 2007)
For the first time, the cultures of aerobic species of fungi and diatoms from spores collected in bottom sediments in the anaerobic hydrogen sulphide zone of the Black Sea at depths from 800 to 2100 m are obtained.